Indirect Activation of Blood Coagulation in Colon Cancer - Wojtukiewicz, Marek Z; Zacharski, Leo R; Memoli, Vincent A; Kisiel, Walter; Kudryk, Bohdan J; Rousseau, Sandra M; Stump, David C (Thrombosis and Haemostasis, 1989)
Systemic activation of the coagulation mechanism is known to exist in patients with colon cancer. The mechanism of such activation was investigated using immunohistochemical techniques applied to fresh frozen sections of resected primary colon cancer specimens. Tumor cells stained for tissue factor, factor V, and urokinase-type plasminogen activator. Perivascular and intercellular areas stained for fibrinogen and the “a” subunit of factor XIII. Staining was minimal or absent for protein C, protein S, plasminogen activator inhibitors 1-3, factor VII, factor X, and fibrin (the antigenic site on the amino-terminal portion of Bβ chain that is exposed following thrombin cleavage of fibrinopeptide B was not detected). The lack of an intact thrombin- generating pathway in situ associated with viable colon cancer cells is consistent with the findings of others that coagulation activation in colon cancer may be triggered by a soluble tumor product that exerts its effect at sites distant from the tumor. These results may explain the absence of clinical responsiveness of colon cancer to antithrombotic drug therapy and may clarify therapeutic strategies for this common tumor.
Keywords: Blood coagulation; Colon cancer